The Structure of Leadership: Presidents, Hierarchies, and Information Flow. - Rudalevige, Andrew (Presidential Studies Quarterly, 2005)
This article draws on various theories of organization and hierarchy to argue that presidential staff may be conceived as a necessary limiting structure on an otherwise chaotic informational environment. As such, the shape of that structure shapes the kind, caliber, and amount of information presidents receive on policy matters. Melding classic organization theory and recent formal work with earlier hypotheses about staff effectiveness, I argue that informational institutions centered on functional rather than specific policy lines will best serve the president, and that parallel processing and other monitoring mechanisms will also help the president obtain good advice. Evidence from the Truman, Reagan, and Bush 11 administrations is used to illustrate this theory and sketch a more systematic research agenda. Reprinted by permission of the publisher.